The Critical Success Factors (CSFs) of managing businesses: a comparison study between the Malaysian and Indonesian entrepreneurs in the franchise industry / Ahmad Asri Abd Samat, Shaira Ismail and Norhayati Mohamad Noor - Abd Samat, Ahmad Asri; Ismail, Shaira; Mohamad Noor, Norhayati (2009)
This research is initiated to explore the Critical Success Factors (CSFs) which are crucial for businesses in order to sustain in a competitive business environment amongst the Malaysian and Indonesian franchisees. As to gather the information, the researchers have identified several CSFs as a benchmark so that we could analyse its relationships to the successful criteria of doing business. Our hypothesis is that, Malaysian and Indonesian franchisees are differed in their business approaches and perceptions towards the business competitive advantage. We also examined the six aspects of business competitive advantage; financial, physical, human, product, customer and competition aspects to make a rationale comparison between Malaysian and Indonesian franchisees in maintaining their business survival.